Identification and characterisation of the early differentiating cells in neural differentiation of human embryonic stem cells - Noisa, P.; Ramasamy, T.S.; Lamont, F.R.; Yu, J.S.L.; Sheldon, M.J.; Russell, A.; Jin, X.; Cui, W. (Public Library of Science, 2012)
One of the challenges in studying early differentiation of human embryonic stem cells (hESCs) is being able to discriminate the initial differentiated cells from the original pluripotent stem cells and their committed progenies. It remains unclear how a pluripotent stem cell becomes a lineage-specific cell type during early development, and how, or if, pluripotent genes, such as Oct4 and Sox2, play a role in this transition. Here, by studying the dynamic changes in the expression of embryonic surface antigens, we identified the sequential loss of Tra-1-81 and SSEA4 during hESC neural differentiation and isolated a transient Tra-1-81(-)/SSEA4(+) (TR-/S4+) cell population in the early stage of neural differentiation. These cells are distinct from both undifferentiated hESCs and their committed neural progenitor cells (NPCs) in their gene expression profiles and response to extracellular signalling; they co-express both the pluripotent gene Oct4 and the neural marker Pax6. Furthermore, these TR-/S4+ cells are able to produce cells of both neural and non-neural lineages, depending on their environmental cues. Our results demonstrate that expression of the pluripotent factor Oct4 is progressively downregulated and is accompanied by the gradual upregulation of neural genes, whereas the pluripotent factor Sox2 is consistently expressed at high levels, indicating that these pluripotent factors may play different roles in the regulation of neural differentiation. The identification of TR-S4+ cells provides a cell model for further elucidation of the molecular mechanisms underlying hESC neural differentiation.